ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN VARIABEL KONTROL UKURAN PERUSAHAAN DAN GROWTH OPPORTUNITY (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2009-2013) - Sinaga, Nobert Steven; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2014)
This study aims to determine the effects of corporate governance mechanism on the financial performance of manufacturing companies with control variables firm size and growth opportunity.Financial performance is proxied by Cash Flow Return On Assets (CFROA) as a measure of financial performance based on the company's operations.The sample in this study were manufacturing companies listed in Indonesian Stock Exchange (IDX) in the periode 2009-2013. The number of sample used were 20 companies listed were taken by purposive sampling. The method of analysis of this research used multiple liniear regression.The result of this research showed thatboard of directors had positive and significat influence to CFROA; board of commissioners and firm size had positive and not significant influence to CFROA; institutional ownership had negative and significant influence to CFROA; meanwhile managerial ownership and Growth Opportunity had negative and not significant influence to CFROA.